Antimicrobial Effect of Quercus robur L. Leaves Selective Extracts from the Mezi Mountain of Djeniene Bourezg (West of Algeria) - Benyagoub, Elhassan; Nabbou, Nouria; Dine, Amal (Current Bioactive Compounds, 2020)
Background: Algeria, by its vast terrestrial extent and its climatic variation, has an abundant, rich and varied flora in which it was counted many aromatic and medicinal species that provide bioactive compounds characterized by their broad biological activities. In this context, this work is based on the evaluation of the antimicrobial activity of Quercus robur L. leaves extracts (Family of Fagaceae). Methods: Firstly, the collected plant material was defatted; then, the extraction of tannins and saponins was carried out according to a standard protocol where the extracts obtained were tested on some uropathogenic microbial strains by disk diffusion method with the determination of the Minimum Inhibitory Concentrations (MICs) by broth macro-dilution method. Results: The extraction yield of the selective extracts was 7.93 and 16.94% for tannins and saponins, respectively. The antibiotic resistance profile of the tested strains showed a resistance relatively important to several antibiotics, namely amoxicillin +clavulanic acid and ampicillin for Escherichia coli, while Pseudomonas aeruginosa showed resistance to amoxicillin+clavulanic acid, amikacin, cefotaxime and ceftazidime. However, Staphylococcus aureus was susceptible to penicillin, gentamicin, ofloxacin and chloramphenicol. Antifungal susceptibility testing has been shown that Candida albicans was susceptible to amphotericin B, econazole and it was clinically categorized as intermediate to miconazole drug. For antimicrobial tests, the tannins and saponins extracts exhibited a low to strong inhibitory effect at tested concentrations lower than 30 mg/mL (ranged from no inhibition to an inhibition zone diameter of 17.5 mm), depending on dose levels and tested microbial strains. Conclusion: This activity is proportional to the tested concentrations, knowing that tannins extract was more active compared to saponins extract. For this, Q. robur could constitute an important source for drug discovery.
Keywords: Quercus robur L. leaves